Edukasi Jejak Digital untuk Meningkatkan Literasi Digital Siswa Kelas VI SDN Gunung 01 Pagi - Marbella, Sarita; Usman, Deriel Akmalio; Febrian, Yusin Arbi; Aldi, Muhammad (Jurnal Pustaka Dianmas, 2025)
The rapid development of digital technology has increased internet usage among elementary school students, yet this trend is not accompanied by adequate digital literacy skills. This condition exposes children to various risks, including a lack of awareness of digital footprints, misuse of personal data (identity theft), and cyberbullying. This community service activity aims to enhance the digital literacy of sixth-grade students at SDN Gunung 01 Pagi through digital footprint education tailored to children’s cognitive development. The activity employed an interactive educational approach, including material presentations, discussions, and question-and-answer sessions using visual media. The results indicate an improvement in students’ understanding of digital footprints, awareness of personal data privacy, and recognition of the consequences of online activities. Students also demonstrated active participation and high enthusiasm throughout the activity. However, the findings revealed a technical skill gap, particularly in creating strong and secure passwords. These results suggest that digital literacy education for elementary school students should be conducted continuously and practically to strengthen both conceptual understanding and technical skills in addressing digital risks.